Mechanistic investigations on multiproduct β-himachalene synthase from Cryptosporangium arvum - Rinkel, Jan; Dickschat, Jeroen S. (Beilstein Journal of Organic Chemistry, 2019)
A bacterial terpene synthase from Cryptosporangium arvum was characterised as a multiproduct β-himachalene synthase. In vitro studies showed not only a high promiscuity with respect to its numerous sesquiterpene products, including the structurally demanding terpenes longicyclene, longifolene and α-longipinene, but also to its substrates, as additional activity was observed with geranyl- and geranylgeranyl diphosphate. In-depth mechanistic investigations using isotopically labelled precursors regarding the stereochemical course of both 1,11-cyclisation and 1,3-hydride shift furnished a detailed catalytic model suggesting the molecular basis of the observed low product selectivity. The enzyme’s synthetic potential was also exploited in the preparation of sesquiterpene isotopomers, which provided insights into their EIMS fragmentation mechanisms.
Keywords: enzyme mechanisms; isotopes; mass spectrometry; promiscuity; terpenes

Enzyme Specificity and Selectivity - Hedstrom, L. (John Wiley & Sons, Ltd., 2010)

(untitled) - Silverstein, R. M.; Rodin, J. O.; Wood, D. L. (Science, 1966)

(untitled) - Zhang, A.; Robbins, P. S.; Leal, W. S.; Linn, C. E., Jr; Villani, M. G.; Roelofs, W. L. (J. Chem. Ecol., 1997)

(untitled) - Christianson, D. W. (Chem. Rev., 2017)

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2016)

(untitled) - Tantillo, D. J. (Angew. Chem., Int. Ed., 2017)

(untitled) - Garms, S.; Köllner, T. G.; Boland, W. (J. Org. Chem., 2010)

(untitled) - Steele, C. L.; Crock, J.; Bohlmann, J.; Croteau, R. (J. Biol. Chem., 1998)

(untitled) - Vedula, L. S.; Jiang, J.; Zakharian, T.; Cane, D. E.; Christianson, D. W. (Arch. Biochem. Biophys., 2008)

(untitled) - Rinkel, J.; Lauterbach, L.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2017)

(untitled) - Pazouki, L.; Niinemets, Ü. (Front. Plant Sci., 2016)

(untitled) - Dixit, M.; Weitman, M.; Gao, J.; Major, D. T. (ACS Catal., 2017)

(untitled) - Rinkel, J.; Dickschat, J. S. (Beilstein J. Org. Chem., 2019)

(untitled) - Dickschat, J. S.; Pahirulzaman, K. A. K.; Rabe, P.; Klapschinski, T. A. (ChemBioChem, 2014)

(untitled) - Saroglou, V.; Dorizas, N.; Kypriotakis, Z.; Skaltsa, H. D. (J. Chromatogr. A, 2006)

(untitled) - Hazzit, M.; Baaliouamer, A.; Faleiro, M. L.; Miguel, M. G. (J. Agric. Food Chem., 2006)

(untitled) - Karioti, A.; Hadjipavlou-Litina, D.; Mensah, M. L. K.; Fleischer, T. C.; Skaltsa, H. (J. Agric. Food Chem., 2004)

(untitled) - Yáñez, X.; Pinzón, M. L.; Solano, F.; Sánchez, L. R. (Molecules, 2002)

(untitled) - Benkaci–Ali, F.; Baaliouamer, A.; Meklati, B. Y.; Chemat, F. (Flavour Fragrance J., 2007)

(untitled) - Yu, Y.; Huang, T.; Yang, B.; Liu, X.; Duan, G. (J. Pharm. Biomed. Anal., 2007)

(untitled) - Zeng, Y.-X.; Zhao, C.-X.; Liang, Y.-Z.; Yang, H.; Fang, H.-Z.; Yi, L.-Z.; Zeng, Z.-D. (Anal. Chim. Acta, 2007)

(untitled) - Mesa-Arango, A. C.; Betancur-Galvis, L.; Montiel, J.; Bueno, J. G.; Baena, A.; Durán, D. C.; Martínez, J. R.; Stashenko, E. E. (J. Essent. Oil Res., 2010)

(untitled) - Bendiabdellah, A.; El Amine Dib, M.; Djabou, N.; Allali, H.; Tabti, B.; Muselli, A.; Costa, J. (Chem. Cent. J., 2012)

(untitled) - Quijano, C. E.; Salamanca, G.; Pino, J. A. (Flavour Fragrance J., 2007)

(untitled) - Heinrich, G.; Pfeifhofer, H. W.; Stabentheiner, E.; Sawidis, T. (Ann. Bot. (Oxford, U. K.), 2002)

(untitled) - Rinkel, J.; Lauterbach, L.; Rabe, P.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Rabe, P.; Rinkel, J.; Dolja, E.; Schmitz, T.; Nubbemeyer, B.; Luu, T. H.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2017)

(untitled) - Rabe, P.; Rinkel, J.; Nubbemeyer, B.; Köllner, T. G.; Chen, F.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2016)

(untitled) - Thulasiram, H. V.; Poulter, C. D. (J. Am. Chem. Soc., 2006)

(untitled) - Lauterbach, L.; Rinkel, J.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Cornforth, J. W.; Cornforth, R. H.; Popják, G.; Yengoyan, L. (J. Biol. Chem., 1966)

(untitled) - Phillips, M. A.; Wildung, M. R.; Williams, D. C.; Hyatt, D. C.; Croteau, R. (Arch. Biochem. Biophys., 2003)

(untitled) - Dickschat, J. S. (Nat. Prod. Rep., 2011)

(untitled) - Srividya, N.; Davis, E. M.; Croteau, R. B.; Lange, B. M. (Proc. Natl. Acad. Sci. U. S. A., 2015)

(untitled) - Hong, Y. J.; Tantillo, D. J. (Org. Biomol. Chem., 2010)

(untitled) - Isegawa, M.; Maeda, S.; Tantillo, D. J.; Morokuma, K. (Chem. Sci., 2014)

(untitled) - Moss, R. A. (J. Phys. Org. Chem., 2014)

(untitled) - Bian, G.; Rinkel, J.; Wang, Z.; Lauterbach, L.; Hou, A.; Yuan, Y.; Deng, Z.; Liu, T.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2018)

(untitled) - Arigoni, D. (Pure Appl. Chem., 1975)

(untitled) - Hong, Y. J.; Tantillo, D. J. (Org. Lett., 2006)

(untitled) - Asuming, W. A.; Beauchamp, P. S.; Descalzo, J. T.; Dev, B. C.; Dev, V.; Frost, S.; Ma, C. W. (Biochem. Syst. Ecol., 2005)

(untitled) - Rabe, P.; Barra, L.; Rinkel, J.; Riclea, R.; Citron, C. A.; Klapschinski, T. A.; Janusko, A.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2015)

(untitled) - Hinkley, S. F. R.; Perry, N. B.; Weavers, R. T. (Phytochemistry, 1994)

(untitled) - Cane, D. E.; Tandon, M. (J. Am. Chem. Soc., 1995)

(untitled) - Hu, Y.; Chou, W. K. W.; Hopson, R.; Cane, D. E. (Chem. Biol., 2011)

(untitled) - Rinkel, J.; Rabe, P.; Garbeva, P.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2016)

(untitled) - Benedict, C. R.; Lu, J. L.; Pettigrew, D. W.; Liu, J.; Stipanovic, R. D.; Williams, H. (J. Plant Physiol., 2001)

(untitled) - Rinkel, J.; Rabe, P.; Chen, X.; Köllner, T. G.; Chen, F.; Dickschat, J. S. (Chem. – Eur. J., 2017)

(untitled) - Rinkel, J.; Lauterbach, L.; Dickschat, J. S. (Angew. Chem., Int. Ed., 2019)

(untitled) - Mitsuhashi, T.; Rinkel, J.; Okada, M.; Abe, I.; Dickschat, J. S. (Chem. – Eur. J., 2017)

(untitled) - Rabe, P.; Klapschinski, T. A.; Dickschat, J. S. (ChemBioChem, 2016)

(untitled) - Rinkel, J.; Rabe, P.; Dickschat, J. S. (Eur. J. Org. Chem., 2019)